Implementing a nurse-enabled, integrated, shared-care model involving specialists and general practitioners in early breast cancer post-treatment follow-up (EMINENT): a single-centre, open-label, phase 2, parallel-group, pilot, randomised, controlled trialResearch in context - Raymond J. Chan; Fiona Crawford-Williams; Chad Yixian Han; Lee Jones; Alexandre Chan; Daniel McKavanagh; Marissa Ryan; Christine Carrington; Rebecca L. Packer; Megan Crichton; Nicolas H. Hart; Emma McKinnell; et al. (EClinicalMedicine)
Summary: Background: Current models of post-treatment cancer care rely heavily on hospital-based, medical specialists and do not sufficiently leverage primary care. Many breast cancer survivors face ongoing unmet needs that may benefit from a multidisciplinary, shared-care approach. We aimed to evaluate the feasibility and preliminary effectiveness of implementing nurse-enabled, shared-follow-up care between the acute and primary care setting for early-stage breast cancer. Methods: In this single-centre, open-label, phase II, pilot, randomised, controlled trial, individuals diagnosed with breast cancer (Stage 0–III) were randomised 1:1 to either usual care or intervention, which includes a 1) Specialist Nurse Consultation to co-develop a survivorship care plan (SCP), 2) Pharmacist Consultation, 3) Case Conference with General Practitioner (GP), and 4) shared follow-up care arrangements. Feasibility and effectiveness outcome measures, including health-related quality of life (primary outcome), physical activity and nutrition, patient experience, and financial toxicity were collected at baseline, and at 3-, 6-, and 12-months, with health service utilisation data at 24-months. Bivariate and multivariable, intention-to-treat analyses were conducted. This trial is registered at Anzctr.org.au (ACTRN12619001594112). Findings: From 3rd December 2019 to 13th April 2021, 61 participants were randomised (intervention n = 29; usual care n = 32); mean age 62.9 standard deviation (SD) = 10.9 years. The intervention was feasible with 100% completion rates across all elements of the specialist nurse consultation and GP case conference. Evaluation of the 28 SCPs indicated the top three goals were exercise (n = 23), diet (n = 12) and mental well-being (n = 11). All care goals can be supported by GPs. No differences were observed between groups for health-related quality of life and the other effectiveness outcomes measures listed above at all timepoints (P > 0.05 for all). There were significantly fewer average post-treatment radiation oncology appointments per patient in the intervention group compared to the control group (0.69 versus 1.27, P = 0.013) at 24-months. Number of unplanned hospital presentations at 24-months were low across both intervention (n = 7) and control (n = 4) groups. Interpretation: Nurse-enabled, shared-care arrangements for women with early-stage breast cancer is feasible, and is as safe as specialist-led model of care. It may provide a more sustainable model of care in a longer term. GPs can meet the survivorship care needs identified breast cancer survivors. This trial can inform a large, pragmatic, hybrid effectiveness-implementation trial. Funding: Metro South Health Research Support Scheme Project Grant.